2015
DOI: 10.1158/0008-5472.can-15-0706
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Contributes to Ovarian Cancer Metastatic Success through Increased Lipogenesis, Enhanced Vascularity, and Decreased Infiltration of M1 Macrophages

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of death from gynecologic malignancy, with high mortality attributable to widespread intra-peritoneal (i.p.) metastases. Recent meta-analyses report an association between obesity, ovarian cancer incidence, and ovarian cancer survival, but the effect of obesity on metastasis has not been evaluated. The objective of this study was to use an integrative approach combining in vitro, ex vivo, and in vivo studies to test the hypothesis that obesity contributes to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(108 citation statements)
references
References 47 publications
9
99
0
Order By: Relevance
“…14 Therefore, we applied the suppression of mortality by SMART to screen genes involved in tumor progression. We showed that low expression of the new gene FAM210B attenuated the TSA effects in cancer cells and promoted malignant metastasis through metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…14 Therefore, we applied the suppression of mortality by SMART to screen genes involved in tumor progression. We showed that low expression of the new gene FAM210B attenuated the TSA effects in cancer cells and promoted malignant metastasis through metabolic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it was recently shown that obesity contributes to ovarian cancer metastases formation (38). Adipose tissue is a key component of the ovarian cancer metastatic microenvironment (39, 40).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is a key component of the ovarian cancer metastatic microenvironment (39, 40). Increased body fat enhances tumor cell–mesothelial cell adhesion and promotes intraperitoneal metastatic dissemination (38). As a known hypolipidemic agent, pantethine may influence metastases formation through its hypolipidemic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Peritumoural fat from obese patients with colorectal cancer has increased expression of genes involved in inflammation, including those encoding cyclo-oxygenase-2 (COX2) and peroxisome proliferator-activated receptor gamma (PPARg) compared with nonobese patients [72]. Increased peritoneal ovarian tumour metastatic growth was observed in obese versus control mice, in three different models of DIO, and this was correlated with enhanced vascularity and a decreased M1:M2 macrophage ratio [73]. These data suggest an altered tumour microenvironment influenced by crosstalk between peritumoural fat and tumour cells [68].…”
Section: The Tumour Microenvironment: Role Of Peritumoural Fat and Immentioning
confidence: 99%